An Economic analysis of arterial road project in Indonesia - DARSONO, Dody (KDI School, 2017)
Over the last decade Indonesia has been facing a lack of Infrastructures development. The rapid growth of population, increasing vehicle ownership, and increasing traffic has created the negative externalities such as: air pollution, road noise, congestion and accidents. It has been argued that infrastructure projects provide a great opportunity for economic growth and development on a regional or national basis. It provides people with to access to workplace, social and education services. The Asia Development Bank guidance mentioned the importance of the decision making on road transport development by the integration of the total costs including negative externalities. The decision maker has been aware of the necessity of an economic analysis or evaluation on road investment project. This thesis will examine one case study on road investment project in East Java, Indonesia. This study will present the economic evaluation of road project, using costs and benefits analysis to Indonesian context. Our result shows that compared to existing road, the using alternative road gives better system condition, reduce maintenance cost, accident, travel time saving, more overall net benefit from economic viewpoint, and this project is economically viable. The government of Indonesia should adopt such economic analysis for investment in the road sector and other infrastructure.
Thesis(Master) --KDI School:Master of Public Policy,2017